Association Between Retinol-Binding Protein 4 Levels and Hepatitis C Virus Infection: A Meta-Analysis - Yingying Lin; Xinyu Cui; Na Zhu; Yanyan Li; Peng Wang; Xin Wang; Yunyun Yi; Xin Li (Diseases)
Background and Objectives: The relationship between circulating retinol-binding protein 4 (RBP4) levels and hepatitis C virus (HCV) infection remains unclear. This study aims to systematically assess RBP4 expression in patients with HCV and its correlation with disease severity. Materials and Methods: We searched the Embase, PubMed, and Cochrane databases for relevant studies up to 1 January 2024. This study was registered on PROSPERO (CRD42023489051). Results: Our analysis included eight studies with 2612 participants (1152 controls and 1282 patients with HCV). Overall, RBP4 levels did not significantly differ between patients with HCV and controls (SMD: −0.36; 95% CI: −0.94, 0.23; p = 0.23). However, in a subgroup of Asian subjects, patients with HCV showed significantly lower RBP4 levels (SMD: −0.40; 95% CI: −0.49, −0.31; p = 0.10). Additionally, a negative correlation between RBP4 levels and disease severity was observed across all studied populations. Conclusions: RBP4 levels may vary due to HCV genotype, ethnicity, and environmental factors. In the context of HCV infection, RBP4 levels appear to reflect the severity of disease progression. Our findings indicate that RBP4 could serve as a biomarker for HCV disease progression. Further research is needed to elucidate the complex mechanisms of RBP4 in HCV infection.